ASPEK YURIDIS PENGGUNAAN KARTU ATM (ANJUNGAN TUNAI MANDIRI) - Endang Retnowati (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2002)
The launching of ATM (automatic teller machine), as a setl service banking was widely accepted because of its flexible and efficiency. Unfortunately, a so called flexible and efficient service not always offered a fully safety guarantee. The